2020
DOI: 10.1007/s42154-020-00123-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analyses of Power Electronics Integrated with Vapour Chamber Cooling

Abstract: Insulated gate bipolar transistor (IGBT) power module is used for power switching transistor devices in the power supply and motor control circuits in both hybrid electric vehicles and electric vehicles. The target of heat flux of IGBT is continuously increasing due to the demand for power rating improvements and miniaturisation. Without suitable efficient cooling technologies, excessively high temperature and uneven temperature distribution can cause high thermal stress, eventually leading to severe module fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Results showed that heat could be removed very well, and the hot spots of the components could be successfully eliminated. Chen et al [133,134] developed a novel vapor chamber to reduce the thermal resistance and improve the temperature uniformity of IGBT power modules. Different from a traditional package scheme, the baseplate and TIM were not implemented, and the DBC substrate was directly soldered on the lid of a vapor chamber.…”
Section: Flat Heat Pipementioning
confidence: 99%
“…Results showed that heat could be removed very well, and the hot spots of the components could be successfully eliminated. Chen et al [133,134] developed a novel vapor chamber to reduce the thermal resistance and improve the temperature uniformity of IGBT power modules. Different from a traditional package scheme, the baseplate and TIM were not implemented, and the DBC substrate was directly soldered on the lid of a vapor chamber.…”
Section: Flat Heat Pipementioning
confidence: 99%